Designing a Set of Service-Oriented Systems as a Software Product Line - Medeiros, Flavio Mota; Almeida, Eduardo Santana de; Meira, Silvio Romero de Lemos (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2010: Anais do IV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2010)
Software reuse is crucial for organizations interested in productivity gains and software quality. In this context, Software Product Line (SPL) and Service-Oriented Architecture (SOA) are two reuse strategies that share common goals and can be used together with the purpose of increasing reuse and producing service-oriented systems, customizable to specific customers, faster and cheaper than creating individual systems. In this sense, this work investigates the problem of designing software product lines using service-oriented architectures, and presents a systematic approach to design product lines based on services. The approach provides guidance to identify, design and document components, services, service compositions and their associated communication flows. In addition, an initial experimental study performed with the intention of validating and refining the approach is also depicted demonstrating that the proposed solution can be viable.